Computational logistics second international conference, ICCL 2011, Hamburg, Germany, September 19-22, 2011. proceedings - ICCL (Conference) 2011 Hamburg, Germany); Bose, Jurgen W.; Hau,Hao.; Jahn, Carlos; Shi, Xiaoning; Stahlbock, Robert; Vob, Stefan; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This book constitutes the refereed proceedings of the Second International Conference on Computational Logistics, ICCL 2011, held in Hamburg, Germany, in September 2011. The 26 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on transport services, logistics systems and production, and maritime shipping and container terminals.
Electronic reproduction.
Keywords: Business logistics -- Data processing -- Congresses; Information technology -- Congresses; Information resources management -- Congresses; Electronic books